Online Mining Intrusion Patterns from IDS Alerts - Kai Zhang; Shoushan Luo; Yang Xin; Hongliang Zhu; Yuling Chen (Applied Sciences, 2020)
The intrusion detection system (IDS) which is used widely in enterprises, has produced a large number of logs named alerts, from which the intrusion patterns can be mined. These patterns can be used to construct the intrusion scenarios or discover the final objectives of the malicious actors, and even assist the forensic works of network crimes. In this paper, a novel algorithm for the intrusion pattern mining is proposed which aimsto solve the difficult problems of the intrusion action sequence such as the loss of important intrusion actions, the disorder of the action sequence and the random noise actions. These common problems often occur in the real production environment which cause serious performance decrease in the analyzing system. The proposed algorithm is based on the online analysis of the intrusion action sequences extracted from IDS alerts, through calculating the influences of a particular action on the subsequent actions, the real intrusion patterns are discovered. The experimental results show that the method is effective in discovering pattern from the complex intrusion action sequences.